ANALISIS YURIDIS TERHADAP PUTUSAN PENGADILAN HUBUNGAN INDUSTRIAL ATAS PERSELISIHAN PEMUTUSAN HUBUNGAN KERJA (PHK) DENGAN ALASAN MENGUNDURKAN DIRI (Studi Kasus Putusan Mahkamah Agung Nomor : 37 K/Pdt.Sus/2013) - Ardiantha Putera Sembiring; Budiman Ginting; Agusmidah Agusmidah; Mahmul Siregar (Universitas Sumatera Utara, 2015)
ABSTRACT Arrangements Termination of Employment by reason of resigned of their own accord have been set in Article 162 of Law Number 13 of 2003 on labor, where in one of the verses that paragraph (3) sets the terms of PHK by reason of resignation in a way apply for resignation by workers/labourers in writing no later than 30 days before the start date of resignation. Against the ruling of the PHI Number: 60/G/2012/PHI.Mdn stating PHK of the plaintiffs are characterized as Termination of Employment since the resignation of their own accord are contrary to Article 162 of Law Number. 13 of 2003 on Labor. Therefore, the decision of the Supreme Court the case Number. 37K/PDT.SUS/2013 quashed the verdict of the Court at the level of industrial relations and stated the Tribunal Judges of PHI had been wrong to apply the law and not paying close attention to disconnect the evidences in the matter, is in compliance with the provisions of applicable law. Keywords : Termination of Employment by reason of resignation, the ruling of PHI, workers/labourers.